Sophia, A Female Robot With Artificial Intelligence In View of Sociology of Government - Ratna Indriasari; Amalia Syauket (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Sophia, a humanoid robot in the form of a woman who is equipped with artificial intelligence Sophia is good at numbers, performing repetitive tasks, interacting, communicating, and displaying attractive facial expressions. numbers, performing repetitive tasks, interacting and communicating in an interesting way as well as displaying facial expressions with various emotions. facial expressions with various emotions. AI in the context of sociology has unwittingly changed social life. social life. The existence of AI in the implementation of e-Government changes the pattern of communication in public services, affecting the socio-cultural ties that exist in the society. services, affecting previously strong socio-cultural ties and forming new communities. This phenomenon reflects the parameters of modernity, indicating changes in the order of the social system due to technological interference. This qualitative research aims to find out how the form of Social Interaction in Artificial Intelligence-Based Public Services (AI)-based Public Services is formed. Social Interaction of Artificial Intelligence-Based Public Services (AI) from the perspective of the sociology of government? The results The results concluded that AI is able to complete work without direct human interaction, or directly with humans. The use of AI technology in public services has potential benefits, such as increasing efficiency, service quality, and benefits for the community. Through the system Automated Customer service, Big Data Analysis for Decision Making, Security Detection Kiiminal Detection, Efficient Transportation Administration, Better Health Care and Diagnosis Society is increasingly responsive to the utilization of AI in public services, this is driven by increasing public awareness of the benefits of AI and the risks associated with AI utilization, such as loss of workers.